2004
DOI: 10.2355/isijinternational.44.957
|View full text |Cite
|
Sign up to set email alerts
|

Potentialities of Simultaneous Removal of Tin and Copper from Molten Iron through Evaporation

Abstract: The Knudsen-cell mass spectrometry was used to study evaporation and thermodynamics of pure liquid Sn, Fe-Sn and Fe-Cu-Sn molten alloys containing up to 20.3 mol% Sn or up to 5 mol% Cu and Sn in a wide temperature range. The thermodynamic properties of the binary melt were approximated by means of the subregular solution model with temperature dependent parameters. The properties of the ternary melt were represented with accuracy not worse than the experimental one by combination of the characteristics of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…According to other studies [24][25][26][27], during reduced pressure treatment, the evaporation forms of the tramp elements Cu and Sn from molten iron or steel containing a high S content are primarily CuS (g) and SnS (g) , and the evaporation is a second-order reaction. Moreover, when the S content in molten iron or steel is low, the evaporations of Cu and Sn are a first-order reaction, and their evaporation forms are mainly Cu (g) and Sn (g) .…”
Section: Reaction Order Of Sb Evaporationmentioning
confidence: 99%
“…According to other studies [24][25][26][27], during reduced pressure treatment, the evaporation forms of the tramp elements Cu and Sn from molten iron or steel containing a high S content are primarily CuS (g) and SnS (g) , and the evaporation is a second-order reaction. Moreover, when the S content in molten iron or steel is low, the evaporations of Cu and Sn are a first-order reaction, and their evaporation forms are mainly Cu (g) and Sn (g) .…”
Section: Reaction Order Of Sb Evaporationmentioning
confidence: 99%
“…Nevertheless, Zaitsev et al [61] indicated that the efficiency of removing tin by vapor pressure processes is low. At the same time, if the vapor pressure process is used in actual production, the pressure in the furnace should be kept low.…”
Section: Vapor Pressure Processmentioning
confidence: 99%
“…Conventional methods for the removal of heavy metal ions from solutions include chemical precipitation [4], ion exchange [5], electrochemical treatment [6], membrane technology [7] and evaporation [8]. However, most of these methods have no selectivity when used in practice and have the disadvantage of high operating cost and more volume of sludge [9].…”
Section: Introductionmentioning
confidence: 99%